DEIXIS IN INAUGURATION SPEECH OF PRESIDENT SUSILO BAMBANG YUDHOYONO - Rafika Purba (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2015)
AbstractThis research deals with the English deixis. The problems of this research are to explain the types of deixis is most dominat found in Inauguration Speech of President Susilo Bambang Yudhoyono, to find out the process of deixis in inauguration speech and to find out the reason of deixis in inauguration speech of President Susilo Bambang Yudhoyono are in such a way. The objectives of this research are to find out the dominant types of deixis, to know the process of deixis and to know the reason of using deixis in the speech of President Susilo Bambang Yudhoyono. This research uses the content analysis qualitative research design. The source of the data is the inauguration speech of President Susilo Bambang Yudhoyono. The technique for collecting data is documentary technique. The instrument for collecting data is documentary sheet. And the technique for analysing data is content analysis. The findings show five types of deixis in the first and the second inauguration speech. From the analysis of the inauguration speech tends to use personal deixis as the dominant type of deixis. In the first inauguration speech, President Susilo Bambang Yudhoyono is dominant uses plural pronoun “kita(we)”, while in the second inauguration speech, President Susilo Bambang Yudhoyono uses first Personal Pronoun “saya (I)”. The reasons of using deixis in inauguration speech of President Susilo Bambang Yudhoyono are to point out or to indicate someone or thing to get information clearly from the inauguration speech. Key words : Deixis, Speech